Case Report: Rare invasive aspergillosis with brain abscess in a non–classically immunosuppressed patient, and pooled analysis of individual patient data (2000–2024) - Regmi, Moksada; Liu, Shikun; Dai, Yuwei; Ye, Jingyi; Chen, Xiaodong; Yang, Jun; Yang, Chenlong (Frontiers in Surgery, 2025)
Intracranial aspergillosis is uncommon but often lethal, especially in classically immunocompromised hosts. We report a 71-year-old man with poorly controlled diabetes (a non-classical risk factor) who developed bilateral frontal abscesses due to Aspergillus fumigatus. After an initial craniotomy with negative cultures and galactomannan, recurrent disease was confirmed by stereotactic biopsy with next-generation sequencing (NGS). Targeted azole therapy (voriconazole, isavuconazole) and multidisciplinary care led to marked clinical and radiographic improvement. We also pooled 343 published cases (2000–2024): overall mortality was 34.6%, and 21.8% among patients without classical immunosuppression (including some with non-classical factors such as diabetes). Improved survival in recent decades likely reflects earlier diagnosis and broader azole use, though inference is limited by case-based evidence. Early tissue diagnosis (including molecular testing), timely surgery when indicated, and CNS-penetrant azoles can yield favorable outcomes in non-classically immunosuppressed patients.